ADAPTIVE STRATEGIES OF TOURISM ENTERPRISES IN THE CRISIS CAUSED BY GLOBAL SECURITY FACTORS - Barvinok, N. V. (The actual problems of regional economy development, 2023)
The article examines the importance of adaptation strategies of tourism business enterprises in the context of the crisis caused by global security factors, which today prevent the tourism sector from fully functioning, especially on the territory of Ukraine. The influence of security factors on the tourism industry of Ukraine at the global level always occurs, however, during the period of the Russian-Ukrainian war and the pandemic, it reached a very high level and caused huge losses. Such conditions of a tourism business enterprise require constant adaptation to the external environment in order to maintain its competitiveness and continue to work in an aggressive market environment. The application of adaptation strategies of tourism business enterprises in crisis conditions is one of the important points for their implementation, exit from the crisis and further development. The purpose of the article is to research and substantiate the importance of adaptation strategies of tourism business enterprises in the context of the crisis caused by global security factors. Research methods. To achieve the goal, the dialectical method of cognition, methods of analysis, synthesis and comparison, system, abstract-logical, modeling method, graphic method and system-structural method were used. The theoretical base of the study consists of the scientific works of domestic and foreign scientists on the problem of the impact of the crisis on tourism business enterprises, the application of anti-crisis management and the adaptation of tourism business enterprises to external influences. The results. In separate articles on the basis of the developed literature of foreign and domestic scientists regarding the importance of adaptation strategies of tourism business enterprises in crisis conditions, it was shown that the majority of source authors pay attention to the importance of adaptation of enterprises to external conditions affecting the enterprise. Global security factors are considered as a factor of the external macro-environment that affects the activities of tourism business enterprises and causes the emergence of a crisis. The adaptation strategy is defined as the direction of adaptation of tourism business enterprises to the action of the external macro-environment, and it is established that in today's conditions, the creation of safe conditions for both tourists and employees of tourism business enterprises takes place.